Unities of Law and the State - Chen, Li-Kung (Trinity College Dublin. School of Law. Discipline of Law, 2021)
This thesis is a study of the composition of state and legal system and their relation, with a particular focus on their configuration as a group which can act as an agent. It seeks to contribute to legal philosophy and constitutional theory by offering a new analytic framework based on the argument that state and law are each constituted by a distinct group agent, to improve the explanation of the 'unity' of the composite and dynamic realities that comprise respectively a state and a legal system. The thesis comprises four distinct and related parts. The first part concerns a state's momentary unity, exhibited by its capacity to act as a group for a particular end on a particular occasion. I argue that it is both possible and reasonable that a state acts as a group agent when carrying out some of its characteristic activities, while rejecting the contention that such massive agency can be achieved only by adopting a unanimity-free understanding of groups. The second part concerns a legal system's momentary unity, which I argue is grounded by legal officials' integration as a group agent. Such strong integration allows a legal system to cooperate or even overlap with other legal systems while retaining a clear identity; it is also argued that law need not depend for its unity on the state and can indeed differ from it. The third part concerns the continuity of a state. I argue that a state depends for its continuous identity on a standing group intention upheld by successive members, which is at no time disrupted by sudden radical change in membership composition. Against major existing views, I demonstrate that a state can survive constitutional and legal discontinuities, and such capacity need not rely on a national community. In addition, a possible continuity-independent ground for the continuity of state responsibility is identified. The fourth part concerns the continuity of legal system. Legal officials' standing intention to maintain the continuous operation of a legal system, I argue, grounds the legal system's continuous identity. In comparison with the reigning view, which ties the continuity of a legal system to the continuity of the state, my account better accords with observations of law's and state's separable continuities, and explains how such developments are possible because of legal officials' distinct joint self-understanding and practice. The upshot of the series of analyses is this. Unities of law and the state are two fundamentally distinct phenomenon; any attempt to reduce one to the other is misguided.
APPROVED
Keywords: legal system; state; unity; identity; continuity; group agency